2017
DOI: 10.5860/crl.78.3.16590
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Roles: Canadian Academic Librarians Embedded in Faculty Research Projects

Abstract: Academic librarians have always played an important role in providing research services and research-skills development to faculty in higher education. But that role is evolving to include the academic librarian as a unique and necessary research partner, practitioner, and participant in collaborative, grant-funded research projects. This article describes how a selected sample of Canadian academic librarians became embedded in faculty research projects and describes their experiences of participating in resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 6 publications
0
15
0
3
Order By: Relevance
“…From the health librarian aspects, our study demonstrated that bibliometrics analysis could support librarians performing many services required by a state of the art health library. By using techniques and tools employed in our study, they may become partners in research (Bedi & Walde, 2017; Brahmi & Kaplan, 2017), consultants (Eddy & Solomon, 2017) and data librarians (Koltay, 2017). By integrating quantitative aspects to qualitative research, they may add rigour to research (Sheffield, Refolo, Petanceska, & King, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…From the health librarian aspects, our study demonstrated that bibliometrics analysis could support librarians performing many services required by a state of the art health library. By using techniques and tools employed in our study, they may become partners in research (Bedi & Walde, 2017; Brahmi & Kaplan, 2017), consultants (Eddy & Solomon, 2017) and data librarians (Koltay, 2017). By integrating quantitative aspects to qualitative research, they may add rigour to research (Sheffield, Refolo, Petanceska, & King, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Goulart and Bedi (2017) Conducted a study in Portugal to examine the effectiveness of public versus private schools by taking the labor market earnings as a measure of effectiveness and controlling the personal characteristics and school choice. The findings showed that private school had an advantage of better performance as compared to public school (Bedi & Walde, 2017;Chelanga, 2016) research on what determines education quality in Sub-Saharan Africa (SSA) identified classroom factors (time, instructional strategies grouping procedures,) school factors (leadership, emphasis on academic achievement and staff development) enable and reinforce, system factors provide direction, and community factors (home environment, support for education) ensure local relevance and ownership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, their role is transforming; for instance, Canadian university librarians have a major share in conducting research projects as the major researcher and also cooperating with faculty members. [ 6 ] Nevertheless, there are many obstacles in the Iranian university libraries; these obstacles include the librarians' poor research skills and knowledge, and the managers' carelessness about these deficiencies. [ 7 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%